Factors influencing computer attitude of library staff of the De La Salle University library - Ramos, Marian S.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
As computer literacy and computer use become more and more important in library systems, the attitude of library staff towards computers play an important role in the successful implementation of computerization. The study examined the attitudes of library staff of the De La Salle University Library towards computers and explored the effects of their age, sex, educational attainment, computer experience, position classification and library department on their attitudes toward computers.
The design of this study used the questionnaire survey to collect data investigating the relationships between the library staff's attitudes toward computers and their personal characteristics. The sample of this study is 49 library staff of the De La Salle University Library. Two questionnaires were used for this study. The Computer Attitude Scale (CAS) developed by Loyd and Gressard was used for measuring the attitudes toward computers of the library staff. It measures attitude based on the following four subscales: (1) computer anxiety, (2) computer confidence, (3) computer liking and (4) computer usefulness. The main scale and its four subscales were used to measure attitude based on staff's: (a) age, (b) sex, (c) educational attainment, (d) computer experience, (e) position classification and (f) library department. The Computer Anxiety Rating Scale (CARS) developed by Rosen, Sears and Weil was administered to measure the computer anxiety of the library staff. The collected data were analyzed by using the Statistical Package for Social Science (SPSS). Analysis of Variance (ANOVA) and regression analysis were conducted for scores on computer attitude and its sub scores on each of the factors examined in the current study.
The study found that the overall computer attitude of library staff is high. Results indicated that the majority of staff surveyed have a low (using CAS) and high (using CARS) anxiety, high confidence, low liking and high usefulness toward computers. CAS' results indicated that computer experience is positively correlated with computer attitude, computer anxiety, computer confidence and computer usefulness at the 0.05 alpha level. Using CARS, it was found that sex and department had significant correlation with library staff's computer anxiety. Females are said to be less anxious than males. Position classification was found to be a significant factor influencing the level of computer usefulness of library staff. Among staff, the higher the position the higher the level of computer usefulness. None of the independent variables was shown to have a significant relationship with computer liking.
The current study confirmed the results of many previous studies that claim computer experience is important in determining computer attitudes specifically anxiety, confidence and usefulness. However, this study rejects that sex had no significant correlation with computer anxiety of library staff. The researcher of the current study suggests that library administrators should design computer training program for the library staff that could be a great help for them to educate themselves as well as to improve their attitude towards computers for the maximum success of library automation.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Computer literacy -- Philippines -- Manila; De La Salle University Library; Librarians -- Philippines -- Manila